Human Rights and Digitization of Law in Phylosophy Perspective - ÜMÜTLÜ, Ayşe Yaşar (Cyberpolitik Journal, 2021)
This study philosophically puts forward the debates about possible human rights violations and ethical problems that digitalized law may cause, while increasing the benefits it provides to society on one side. Law has defined human rights in the process of evolving from the stage reached by the rationalization movements in the enlightenment and modernism period of European History to today’s digitalization and has carried it into the constitutional texts of many countries in the universal sense. However, besides rationalization, while the developments in science and technology achieved great success, it was based on a positivist perspective that isolates itself in producing solutions to ethical problems. Therefore, it was inevitable that human rights, based on natural law, would conflict with this kind of positivist understanding at the center of technology and science on ethical issues. While facilitating the document processing processes in the field of law with the software produced in the information technologies sector, artificial intelligence judgement, software to determine the crime and criminal profile, and the problems that may arise from these, started to be discussed in the field of human rights over concerns such as "discrimination" and "violation of privacy".